Efeitos ambientais e genéticos sobre escores visuais e ganho em peso ao sobreano de bovinos brangus - Queiroz, S. A. [UNESP]; Oliveira, J. A. [UNESP]; Costa, G. Z. [UNESP]; Fries, L. A. (SciELO Espana/Repisalud, 2013)
This research aimed at studying the effects of age of the cow at calving (IVP), age of the animal at yearling (IDS), the direct additive genetic (AD) and maternal (AM) effects and individual heterozygosity (HI) on visual scores of conformation (CS), early finishing (PS) and muscling (MS) at postweaning and average daily gain from weaning to yearling (GDS) of cattle used to originate the Brangus breed. There were analyzed records on 24 531, 21 166, 24 006 and 25 419 for CS, PS, MS and GDS, respectively, of animals born from 1986 to 2002 belonging to livestock files of Gensys Consultores Associados S/C Ltda. The analyses were performed by the least square method using mathematical models that included contemporary group as class variable and IVP, IDS, AD, AM and HI as covariates. IVP showed linear and quadratic effects (p<0.01) on GDS and linear (p<0.01) on PS, while the quadratic effect of IDS was not significant for PS and GDS. AD and AM were significant (p<0.01) only for PS and MS scores, respectively. All the traits were significantly (p<0.01) influenced by HI. The environmental and genetic effects were important sources of variation for the studied traits and should be taken into account when comparison of animals and selection were performed.
Genetic and environmental affects on visual scores and yearling weight gain of brangus cattle
Keywords: Age of animal at yearling; Age of cow at calving; Conformation; Heterozygosity; Musculature; Precocity